New indolizidine alkaloids from psychrophilic yeast Glyciozyma antarctica PI12 - Rosandy, Andi Rifki; Nadarajah, Wickneswary; Abu Bakar, Muntaz; Cheah, Yoke Kqueen; Mohd. Said, Mohd. Ikram; Al Muqarrabun, Laode Muhammad Ramadhan; Khalid, Rozida (Malaysian Analytical Sciences Society, 2016)
Two alkaloid compounds: namely 3-(1-aminoethyl)tetrahydro-1H-pyrrolo[1,2-d][1,2,4]oxadiazine-1,4(3H)-dione (1) and tetrahydro-1H-pyrrolo[2,1-c][1,4]oxazine-1,3(4H)-dione (2) was isolated from Glyciozyma antarctica (PI12), a psychrophilic yeast. The isolated compounds were isolated by Radial Chromatography and Thin Layer Chromatography techniques. The chemical structures were elucidated by Ultraviolet-visible, Infrared, Nuclear Magnetic Resonance and Mass Spectroscopy.